Effect of Solid Particles on Droplet Size Applying the Time-Shift Method for Spray Investigation - Simon Wachter; Tobias Jakobs; Thomas Kolb (Applied Sciences, 2020)
This study investigated the influence of solid particles on primary breakup and resulting droplet size for different process parameters. Two sets of Newtonian fluids (each consisting of one pure liquid and one suspension at the same respective viscosity) were used, for isolated investigation of solid particles on spray formation independent of liquid viscosity. The spray was recorded by a high-speed camera and a SpraySpy® system based on the time-shift effect, while a commonly used Spraytec® laser diffraction analyzer was employed for validation. An external-mixing twin-fluid atomizer was operated at different gas velocities and corresponding GLR at constant liquid mass flow. For the investigated suspensions an increased Sauter mean diameter was detected, compared to the pure liquids with identical dynamic viscosity. This effect was explained by the tensile strength stabilizing the suspension droplets.